Comparison of Subjectively Perceived Pro-Health Effects of Practicing Various Forms of Body & Mind Training in Women - Katarzyna Ustarbowska; Bartosz Trybulec; Paweł Jagielski (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
Background: Body & mind trainings are forms of aerobics, the aim of which, apart from improving physical fitness, is to additionally provide mental relaxation. The aim of this study was a comparison of physical and mental pro-health effects from practicing Hatha yoga, Pilates and bodyART. Material and methods: Our own self-assessment questionnaire was used assess the impact of selected forms of body & mind training on the physical and mental fitness of people regularly practicing the forms. A group of 81 women practicing Hatha yoga, Pilates or bodyART for a minimum of 2 workouts per week were qualified. Additional inclusion criteria involved at least a 2-month training period and not practicing the other sport disciplines in study period. Results: After regular body & mind training, significant beneficial changes involving primarily the reduction of joint pain and increased flexibility were subjectively noticed by the participants. Changes included a significant reduction of back pain for Hatha yoga and Pilates and reduction of knee pain and improvement of the sense of balance for bodyART. Conclusions: Practicing body & mind forms has a beneficial impact on the perception of psychophysical health, regardless of the type of training, while the bodyART form generally showed the greatest number of effects.